(untitled) (MAUSAM, 1958)
This paper describes a method of producing a frequency Shift keying transmitter and the method together an of adapting it for use with the F-type rawinsonde. The frequency shift keying is produced by a short copper strip placed at a distance of two inches from the transmitter. The rawinsonde thus developed retains the essential simplicity of the single valve transmitter. Its special feature is the steady signal for direction finding, providing at the same time, the F-type radiosonde signals which are translated into the records on the paper tape as usual.